Evaluation on trend towards the performance for cocoa industry in Malaysia (1981-2005) / Nur Akmarina Mohd Nashoha (Faculty of Business and Management, 2007)
In Malaysia, there are a lot of activity involving export and import of many types of commodity. One of these commodities is cocoa. Cocoa plantation has successfully conquered all countries and continents of the world in just over 500 years since it's first discovered. But in South East Asia the Spanish first introduced cocoa in the 17th century. And in Malaysia, the cocoa was first planted in Malacca in 1778. And the earliest cocoa commercialization started between 1853 to 1959. But nowadays, cocoa was not being given much attention as other main commodities. Focus is more given to core commodities such as oil. Thus, it is important for us to look at the performance of cocoa industry in Malaysia in order to ensure that this industry may survive. Because of that, three factors will be studied in this research to look at Malaysia cocoa industry performance. The framework for this research integrates three categories of factors influencing on cocoa industry in Malaysia, which are, Export of Cocoa, Import of Cocoa and World Cocoa Production by other competitors. The model was tested by viewing 25 years of export, import and world production (n=25). There are some problems occurred with the trend of cocoa industry in Malaysia. The Malaysia cocoa industry is experiencing a downward trend. This is due to some reasons. Although the export of cocoa is increasing, the trend for cocoa import is also increasing. The trend for import of cocoa in Malaysia has increase since there is an increase in the demand for cocoa by Malaysia planters. This happen because of lack of cocoa plantation areas that cause to lower cocoa supply. Thus, Malaysia cocoa planters need to get cocoa supply from other cocoa producing countries in order to produce more cocoa-based products. This had cause to an increasing trend in cocoa import. Besides, the trend for cocoa export is also increasing since there is an increase in the demand for other cocoa-based products. Malaysia has increase in the export of cocoa-based products but we still need to import cocoa from other countries since there is lack of cocoa supply in Malaysia. There is a counter-trading occur here. The research objectives are to identify the trend for export and import of cocoa in Malaysia and also to identify whether there is relationship between world cocoa production and the performance of cocoa industry in Malaysia. The research methodology used in this research is analyzing a secondary data. To identify the trend, all the data will be analyzed using graph build from Excel application. On the hand, the relationship will be analyzed using correlation and regression in SPSS.The findings in the research shows that the trend for cocoa export in Malaysia is increasing and this is the same for the trend for cocoa import in Malaysia. On the other hand the trend for Malaysia cocoa industry Is decreasing since there is an increase in both export and import of cocoa when counter-trading occurred. Meanwhile, findings also showed that there is a low relationship between world cocoa production and cocoa industry in Malaysia where world cocoa production did not give much affect t cocoa industry in Malaysia.